1986
DOI: 10.1021/bi00362a010
|View full text |Cite
|
Sign up to set email alerts
|

Molecular structure of rat brain apamin receptor: differential photoaffinity labeling of putative potassium channel subunits and target size analysis

Abstract: Two photoreactive apamin derivatives were prepared with an aryl azide [[(azidonitrophenyl)amino]acetate (ANPAA)] group coupled at different positions on the neurotoxin molecule. These ligands were used to identify membrane components in the environment of the neuronal binding site that is associated with a Ca2+-activated K+ channel. 125I-[alpha-ANPAA-Cys1] apamin labeled a single Mr 86 000 chain in cultured neurons whereas two bands corresponding to Mr 86 000 and 59,000 were detected in synaptic membrane prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
25
1

Year Published

1987
1987
1998
1998

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 31 publications
8
25
1
Order By: Relevance
“…This polypeptide has also been covalently labeled in both intact cultured neurons and synaptic membranes from rat brain [9,10] and target size analysis suggests that this chain carries the binding site [lo]. A second polypeptide of 57-kDa was detected in liver but not in smooth or cardiac muscle.…”
Section: Resultsmentioning
confidence: 99%
“…This polypeptide has also been covalently labeled in both intact cultured neurons and synaptic membranes from rat brain [9,10] and target size analysis suggests that this chain carries the binding site [lo]. A second polypeptide of 57-kDa was detected in liver but not in smooth or cardiac muscle.…”
Section: Resultsmentioning
confidence: 99%
“…They served and disulphide-bond pattern, into seven groups, which generally reflect their natural origin : scorpion toxins of 31Ϫ39 amino as molecular calipers to measure the dimension of the outer vestibule of the pore of particular channels [40Ϫ47]. Furthermore, acids [9]; dendrotoxins from mamba snakes and kalicludines from sea anemone, of 57Ϫ60 amino acids [10Ϫ12] ; small pep-they were used for the purification, isolation [24, 48Ϫ50] and pharmacological classification of K ϩ channels [8], and to study tides of 18Ϫ22 amino acids isolated from bee venom, including mast-cell-degranulating peptide and apamin [13] ; sea anemone the tissue distribution [51,52] and physiological role [4,5] of individual channel subtypes. Since each K-toxin presents an intoxins of 35Ϫ37 amino acids [14]; the complex group of phospholipase A 2 toxins [15] from snake venoms, including crotoxin, dividual pattern of selectivity and specificity towards the vast array of existing K ϩ channels, the discovery of new toxins may notexin and beta-bungarotoxin [16] ; the hanatoxins of 35 amino acids isolated from spider venom [17]; and κ-conotoxin PVIIA, provide valuable tools for their further study.…”
mentioning
confidence: 99%
“…Apamin passes the blood/brain barrier where its site of action is the central nervous system (Habermann and Cheng-Raude, 1975). Banks et al (1979) discovered recently that apamin acts as a specific blocker of a calcium-dependent potassium channel in guinea-pig taenia coli and in liver, implying that apamin receptors are also located in the periphery.Receptor characterization was first made possible by the availability of a pure '251-labelled derivative of apamin (Hugues et al, 1982a) and later by the availability of two wellcharacterized photosensitive probes of '251-labelled apamin (Seagar et al, 1985(Seagar et al, , 1986. Studies on various tissues revealed a unique receptor in the rat central nervous system (Seagar et al, 1986), guinea-pig smooth muscle, liver and rat heart (Marqu2ze et al, 1987), which was composed of several protein subunits.…”
mentioning
confidence: 99%
“…Receptor characterization was first made possible by the availability of a pure '251-labelled derivative of apamin (Hugues et al, 1982a) and later by the availability of two wellcharacterized photosensitive probes of '251-labelled apamin (Seagar et al, 1985(Seagar et al, , 1986. Studies on various tissues revealed a unique receptor in the rat central nervous system (Seagar et al, 1986), guinea-pig smooth muscle, liver and rat heart (Marqu2ze et al, 1987), which was composed of several protein subunits.…”
mentioning
confidence: 99%
See 1 more Smart Citation